Different Bacteroides Species Colonise Human and Chicken Intestinal Tract - Kollarcikova, Miloslava; Faldynova, Marcela; Matiasovicova, Jitka; Jahodarova, Eva; Kubasova, Tereza; Seidlerova, Zuzana; Babak, Vladimir; Videnska, Petra; Cizek, Alois; Rychlik, Ivan (Microorganisms, 2020)
Bacteroidaceae are common gut microbiota members in all warm-blooded animals. However, if Bacteroidaceae are to be used as probiotics, the species selected for different hosts should reflect the natural distribution. In this study, we therefore evaluated host adaptation of bacterial species belonging to the family Bacteroidaceae. B. dorei, B. uniformis, B. xylanisolvens, B. ovatus, B. clarus, B. thetaiotaomicron and B. vulgatus represented human-adapted species while B. gallinaceum, B. caecigallinarum, B. mediterraneensis, B. caecicola, M. massiliensis, B. plebeius and B. coprocola were commonly detected in chicken but not human gut microbiota. There were 29 genes which were present in all human-adapted Bacteroides but absent from the genomes of all chicken isolates, and these included genes required for the pentose cycle and glutamate or histidine metabolism. These genes were expressed during an in vitro competitive assay, in which human-adapted Bacteroides species overgrew the chicken-adapted isolates. Not a single gene specific for the chicken-adapted species was found. Instead, chicken-adapted species exhibited signs of frequent horizontal gene transfer, of KUP, linA and sugE genes in particular. The differences in host adaptation should be considered when the new generation of probiotics for humans or chickens is designed.
Keywords: microbiome; human; microbiota; pentose cycle; glutamate decarboxylase; Bacteroides; caecum; chicken